PATH-04. MDM2/4 AMPLIFICATION AND RISK OF HYPERPROGRESSION IN HIGH-GRADE GLIOMAS TREATED WITH CHECKPOINT INHIBITORS - Donovan, Laura (Neuro Oncol, 2018)
Checkpoint inhibitors are revolutionizing cancer treatment. However, there are recent reports of systemic cancer patients treated with checkpoint inhibitors with associated hyperprogressive disease (HPD), a ≥2-fold increase in tumor growth rate at first post-treatment imaging, and worse outcomes. Some reports have suggested that MDM 2/4 amplification in advanced cancer may correlate with higher risk for HPD. MDM2/4 amplifications are relatively common and are reported in up to 20% of glioblastomas. We performed a retrospective review to assess the association between MDM2/4 amplification and HPD in patients with high grade gliomas (HGG) treated with immune checkpoint inhibitors. Of 102 patients with HGG at our institution receiving PD1 inhibitors, 13 patients were identified to have MDM2/4 amplification. 5 were treated upfront and 8 at recurrence with PD1 inhibitors. 7/8 patients at recurrence received concurrent bevacizumab. MRIs, prior to and following initiation of checkpoint inhibitor therapy, were evaluated for evidence of HPD. 6/13 patients had radiographic progression on the first MRI after initiation of treatment. Of these, 1 met criteria for HPD in the setting of a trial with nivolumab and vorinostat. She later resumed nivolumab and avastin with significant radiographic improvement; however, continued to clinically deteriorate and died 6 weeks later. 4/6 patients had radiographic pseudo-progression with subsequent response or stabilization of disease, 1 with pathologic confirmation after re-resection. 1 continued to progress at a similar rate prior to starting immunotherapy. In this small retrospective cohort, 1 patient with MDM2/4 amplification had evidence of HPD after starting treatment with Nivolumab. However, concurrent treatment with vorinostat limits the ability to draw conclusions. Preliminarily, it does not seem that these patients need to be excluded from checkpoint inhibitors trials. After final collection of progression and survival data, we will compare the rate of progression of MDM2/4 amplified HGG to non-amplified MDM2/4 tumors.